Familial screening for genetic haemochromatosis by means of DNA markers. Issue 5 (May 1992) - Yaouanq, J; el Kahloun, A; Chorney, M; Jouanolle, A M; Mauvieux, V; Perichon, M; Blayau, M; Pontarotti, P; Le Gall, J Y; David, V
Abstract : Genetic haemochromatosis (HFE) is a frequent and potentially fatal disease. Early phlebotomies may prevent complications. The recessive gene for HFE is unknown but closely linked to the HLA-A locus. No direct test for homozygosity for HFE is currently available, apart from HLA typing within the family of a patient with confirmed HFE. During a reverse genetic approach to identify the gene, we found three anonymous genomic probes (P3, P5, and I.82) derived from previously cloned YACs and physically mapped in the HLA class I region. P3 and P5 probes recognise 3 loci (P3A, P3B, P5) and I.82 one locus about 100 kb from HLA-A. Using five biallelic polymorphisms (I.82/BglII, P3B/EcoRV, P3B/PstI, P5/HindIII, P3A/PstI), we tested 198 HLA typed subjects from the families of 22 haemochromatosis patients. The information from the five polymorphisms was sufficient to identify unequivocally extended restriction haplotypes in all families. The restriction haplotypes cosegregate with the HFE allele and enable identification of genotypically identical sibs in all families studied. The linked DNA markers described in this article avoid the disadvantages of HLA serological typing and can be used in genetic counselling of HFE families.